(untitled) (Conference Zone, 2022)
for the creative activity of the designer must have information from many fields of knowledge.To achieve a positive result, the designer must master his knowledge related to the field of art and the direction of science. In each type of art, the ideological-creative basis is composition. In other words, through composition, the designer expresses an idea of interest. Learning to use a creative resource is important in building the composition of a costume project to follow the necessary laws, to increase the creative approach and the ability to visualize. Opinions and reflections on the use of creative resources in the creation of costume design are kept.